EVALUASI PROGRAM PRAKTEK KERJA INDUSTRI UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DAN KESIAPAN KARIR PESERTA DIDIK - Muthi, Ibnu (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The objective of this study is to assess the effectiveness of industrial work practice (prakerin) programs. This study employs a descriptive qualitative technique. The evaluation model employed is the CIPP (Context, Input, Process, Product) evaluation model. Data was gathered through the methods of observation, interviews, and documentation, and subsequently analyzed using the data reduction technique developed by Miles and Huberman. The results of the research show that: (1) The context for implementing internships at Tridaya Bekasi Vocational School is appropriate, in planning, compiling and synchronizing competencies it is necessary to involve DU/DI elements, and the development of internship collaboration through an MoU has not been well realized; (2) the input for implementing internships is appropriate, but participants still need to be prepared in terms of competency, where the obstacles faced by students are more about competency mastery and lack of work readiness, therefore maximizing the time and training materials is very necessary; (3) the process of implementing internships is appropriate, but the supervisor's role and responsibilities are less than optimal, causing communication about student competency development to be poorly monitored; (4) the product for implementing the internship is appropriate, this is shown by the changes that occur in students in terms of attitudes, responsibilities and increased competence.